2015
DOI: 10.1128/jb.02231-14
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus epidermidis SrrAB Regulates Bacterial Growth and Biofilm Formation Differently under Oxic and Microaerobic Conditions

Abstract: e SrrAB expression in Staphylococcus epidermidis strain 1457 (SE1457) was upregulated during a shift from oxic to microaerobic conditions. An srrA deletion (⌬srrA) mutant was constructed for studying the regulatory function of SrrAB. The deletion resulted in retarded growth and abolished biofilm formation both in vitro and in vivo and under both oxic and microaerobic conditions. Associated with the reduced biofilm formation, the ⌬srrA mutant produced much less polysaccharide intercellular adhesion (PIA) and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…Biofilm formation is influenced by environmental factors, including multiple species interactions (Lee et al ., ), as well as transcriptional variation (Wu et al ., ) and phase variation (Brooks and Jefferson, ). However, differences in the genes associated with biofilm formation within species are less well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation is influenced by environmental factors, including multiple species interactions (Lee et al ., ), as well as transcriptional variation (Wu et al ., ) and phase variation (Brooks and Jefferson, ). However, differences in the genes associated with biofilm formation within species are less well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the ⌬srrAB mutant is necessary for anaerobic growth but conversely may be detrimental to survival within an anaerobic environment. It has been suggested that the decreased expression of genes involved in anaerobic metabolism may be responsible for the altered growth and survival of the ⌬srrAB mutant under these conditions (16). For example, the discrepancy between growth and survival may be explained by the dysregulation of the nrdDG and nar operons (17).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a pronounced cell death phenotype associated with the ⌬srrAB mutation (16,17). Given that transcription profiling experiments suggested that the SrrAB regulatory system has a negative effect on cidABC transcription (17) and that medium acidification due to the accumulation of acidic fermentative metabolites can influence cell fate (13), we initially tested the hypothesis that increased cidC-dependent acetate production was responsible for the decreased survival of an S. aureus ⌬srrAB mutant relative to that of the wild-type strain.…”
Section: Disruption Of Srrab Enhances Weak Acid-dependent Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of PIA and extracellular DNA Detection of PIA and eDNA from static biofilms was performed as previously described with a few modifications (Mann et al 2009;Wu et al 2015). Briefly, the dishes were chilled at 4°C for 15 min and 10 ll of 0.5 M EDTA was added.…”
Section: Static Biofilm Assaysmentioning
confidence: 99%